SARS-CoV-2–Associated Myocarditis: A Case of Direct Myocardial Injury. (March 2022) - Verma, Amanda K.; Olagoke, Olakanmi; Moreno, Jonathan D.; Rezaee, Neda; Ma, Pan; Liu, Jing; Javaheri, Ali; Lavine, Kory; Masood, Muhammad F.; Lin, Chieh-Yu
Abstract : Supplemental Digital Content is available in the text.